Complete Book of Remote Access: Connectivity and Security - Kasacavage, Victor (CRC Press, 2009)
As technology advances, the demand and necessity for seamless connectivity and stable access to servers and networks is increasing exponentially. Unfortunately the few books out there on remote access focus on Cisco certification preparation, one aspect of network connectivity or security. This text covers both-the enabling technology and how to make remote access secure.